Solid-state spark plasma sintering of super wear resistant B4C–SiC–TiB2 triplex-particulate composites. Issue 3 (1st February 2023) - Rodríguez-Rojas, Fernando; Zamora, Victor; Guiberteau, Fernando; Ortiz, Angel L.
Abstract: B4 C–SiC–TiB2 ceramic composites with equal volume fractions of the three phases ( i.e., 1B4 C–1SiC–1TiB2 ) were fabricated by solid-state spark-plasma sintering (SPS) from commercially available B4 C, SiC, and TiB2 powders, first optimizing their densification temperature and then investigating for the first time the unlubricated sliding wear of the optimally SPS-ed composite. It is shown that SPS is optimal at 1800 °C (under 75 MPa pressure and 5 min soaking), which is much lower than the temperatures used so far for both the solid-state hot-pressing and SPS of this and other B4 C–SiC–TiB2 composites. It is also shown that the optimally SPS-ed 1B4 C–1SiC–1TiB2 composite has a triplex-particulate microstructure with evenly distributed carbide and boride grains whose sizes are essentially those of the corresponding starting powders, and that it is ultrahard ( i.e., ∼35 GPa) and relatively tough ( i.e., ∼4 MPa⋅m 1/2 ). Moreover, it is demonstrated that, due to its ultra-high hardness and proneness to form a coherent oxide tribolayer, it is also very immune to wear, possessing an unprecedented super wear resistance to unlubricated sliding contact ( i.e., ∼1.6·10 8 (N⋅m)/mm³), thanks to which it only undergoes very mild abrasion in the form of superficial plastic scratches with hardly any material removal by micro-fracture. Finally, implications of interest for the ceramics and hard-materials communities are discussed.